2018
DOI: 10.1590/1678-4685-gmb-2017-0121
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of transposable elements and multigene families: Microstructural variation in Characidium (Characiformes: Crenuchidae) genomes

Abstract: Eukaryotic genomes consist of several repetitive DNAs, including dispersed DNA sequences that move between chromosome sites, tandem repeats of DNA sequences, and multigene families. In this study, repeated sequences isolated from the genome of Characidium gomesi were analyzed and mapped to chromosomes in Characidium zebra and specimens from two populations of C. gomesi. The sequences were transposable elements (TEs) named retroelement of Xiphophorus (Rex); multigene families of U2 small nuclear RNA (U2 snRNA);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Some studies have suggested that the H3 sequences may be dispersed throughout genomes by ectopic recombination, invasion of transposable elements (TE), and/or circular DNA [ 30 , 31 ]. In fishes, Pucci et al [ 64 ] demonstrated that parts of TE may be found in the intergenic regions of histone sequences, and suggested that such elements could help disperse copies of histone genes throughout a genome. Thus, it is likely that the dispersion of histone H3 in the studied species may be associated with TE insertions and/or genetic hitchhiking.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the H3 sequences may be dispersed throughout genomes by ectopic recombination, invasion of transposable elements (TE), and/or circular DNA [ 30 , 31 ]. In fishes, Pucci et al [ 64 ] demonstrated that parts of TE may be found in the intergenic regions of histone sequences, and suggested that such elements could help disperse copies of histone genes throughout a genome. Thus, it is likely that the dispersion of histone H3 in the studied species may be associated with TE insertions and/or genetic hitchhiking.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic genomes contain a high diversity of repetitive DNA sequences [1,2]. The amplification/ deletion of these sequences contributed significantly to the extraordinary variation in genome size found between taxa [3][4][5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of these mechanisms, when we compare different genomes, would be the differentiation of repetitive DNA copies, as verified for these species. Chromosome differentiation caused by the movement of repetitive sequences seems to be very important for speciation 58,[68][69][70] . Symonová et al 58 provided indirect evidence in which rDNA uses the spreading mechanism of retrotransposons, subsequently affecting recombination rates in genomes, leading to rapid genome divergence in close relationship species.…”
Section: Discussionmentioning
confidence: 99%